Agenda setting in the Ecuadorian press: El Universo, El Mercurio, El Comercio and el Telégrafo - Punin Larrea, M. (2017)
Introduction: This study examines the ideology informing the agenda setting of Ecuador s four major newspapers: El Universo, El Telégrafo, El Comercio and El Mercurio. Methods: This study is based on the analysis of nine aspects of the content published from 16 April to 18 May, 2012, by Ecuador s five major newspapers. Results: In the sample of newspapers, public institutions are the main sources of information; the daily routines do not favour investigative journalism; and short news stories are the most predominant form of journalism. Discussion: The lack of investigative journalism is remarkable in the sample of newspapers. Journalists often prefer to follow daily routines with the help of public organisations, which make it easier for them to find newsworthy events. Conclusions: Ecuador s print media are constantly being monitored to determine their contribution to journalism. The work of news media outlets is usually restricted by particular interests.